Successful application of airway pressure release ventilation in a child with severe acute respiratory distress syndrome induced by trauma: a case report - Jing Su; Xin Tie; Yao Chen; Tongjuan Zou; Wanhong Yin (BMC Pulmonary Medicine, 2024)
Abstract Background Trauma has been identified as one of the risk factors for acute respiratory distress syndrome. Respiratory support can be further complicated by comorbidities of trauma such as primary or secondary lung injury. Conventional ventilation strategies may not be suitable for all trauma-related acute respiratory distress syndrome. Airway pressure release ventilation has emerged as a potential rescue method for patients with acute respiratory distress syndrome and hypoxemia refractory to conventional mechanical ventilation. However, there is a lack of research on the use of airway pressure release ventilation in children with trauma-related acute respiratory distress syndrome. We report a case of airway pressure release ventilation applied to a child with falling injury, severe acute respiratory distress syndrome, hemorrhagic shock, and bilateral hemopneumothorax. We hope this case report presents a potential option for trauma-related acute respiratory distress syndrome and serves as a basis for future research. Case presentation A 15-year-old female with falling injury who developed severe acute respiratory distress syndrome, hemorrhagic shock, and bilateral hemopneumothorax was admitted to the surgical intensive care unit. She presented refractory hypoxemia despite the treatment of conventional ventilation with deep analgesia, sedation, and muscular relaxation. Lung recruitment was ineffective and prone positioning was contraindicated. Her oxygenation significantly improved after the use of airway pressure release ventilation. She was eventually extubated after 12 days of admission and discharged after 42 days of hospitalization. Conclusion Airway pressure release ventilation may be considered early in the management of trauma patients with severe acute respiratory distress syndrome when prone position ventilation cannot be performed and refractory hypoxemia persists despite conventional ventilation and lung recruitment maneuvers.